2009
DOI: 10.1002/jms.1623
|View full text |Cite
|
Sign up to set email alerts
|

Tandem mass spectrometry of synthetic polymers

Abstract: The detailed characterization of macromolecules plays an important role for synthetic chemists to define and specify the structure and properties of the successfully synthesized polymers. The search for new characterization techniques for polymers is essential for the continuation of the development of improved synthesis methods. The application of tandem mass spectrometry for the detailed characterization of synthetic polymers using the soft ionization techniques matrix-assisted laser desorption/ionization ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
70
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 62 publications
(115 reference statements)
0
70
0
2
Order By: Relevance
“…Inherent viscosity (η inh ) values were low, especially for PIA-III derived from the diacid III obtained with L-phenylalanine. MALDI-TOF mass spectrometry was used as an essential tool for the characterization of synthetic polymers and determines the absolute molecular weight distributions (24)(25)(26). In the analysis of the PIAs, it was possible to observe m/z signals which were assigned to protonated and sodium forms associated to average molecular mass ranging from 1180 to 3219 m/z ( Table 2).…”
Section: Polymer Synthesismentioning
confidence: 99%
“…Inherent viscosity (η inh ) values were low, especially for PIA-III derived from the diacid III obtained with L-phenylalanine. MALDI-TOF mass spectrometry was used as an essential tool for the characterization of synthetic polymers and determines the absolute molecular weight distributions (24)(25)(26). In the analysis of the PIAs, it was possible to observe m/z signals which were assigned to protonated and sodium forms associated to average molecular mass ranging from 1180 to 3219 m/z ( Table 2).…”
Section: Polymer Synthesismentioning
confidence: 99%
“…Matrix-assisted laser desorption/ionization (MALDI) has become an important analytical technique in the study of a range of compounds, 1 including peptides 2,3 and synthetic polymers, 4,5 from which accurate end-group analysis and molecular weight determination, including both whole mass and sequence information, can be obtained. [6][7][8][9][10][11] Recently, Spengler et al 12 reported that fragment analysis of a variety of compounds generated by the MALDI process can allow linkage information to be obtained by post-source delay (PSD), whereas others have extended this to in-source decay (ISD), 13 electron-capture dissociation, 14 or terminal sequencing 15 , thereby furthering the utility of the MALDI technique.…”
Section: Introductionmentioning
confidence: 99%
“…therewith by far the analytical possibilities in polymer chemistry. [3][4][5] Since then, a large variety of synthetic polymers has been investigated by MALDI-MS methods, such as polystyrene (PS) and poly(methyl methacrylate) (PMMA). Also poly(ethylene glycol) (PEG) is very well investigated by MALDI-MS techniques as it provides an easily ionizable structure.…”
Section: Introductionmentioning
confidence: 99%